“Off-on” aggregation-based fluorescent sensor for the detection of chloride in water() - Watt, Michelle M. (Org Biomol Chem, 2015)
Receptors selective for anions in aqueous media are a crucial component in the detection of anions for biological and environmental applications. Recent sensor designs have taken advantage of systems known to aggregate in solution, eliciting a fluorescent response. Herein, we demonstrate a chloride-selective fluorescent response of receptor 1(+), based on our well-established class of 2,6-bis(2-anilinoethynyl)pyridine bisureas. The fluorescence intensity ratio of 1(+)·Cl(−) aggregates in water is four times larger than the next most fluorescent anion complex, 1(+)·ClO(4)(−). In addition, (1)H NMR spectroscopic titrations demonstrate 1(+) binds chloride more strongly than other biologically relevant anions in solutions of both DMSO-d(6) and 50/50 DMSO-d(6)/MeCN-d(3).